1987
DOI: 10.1002/1097-0142(19870401)59:7<1274::aid-cncr2820590708>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced neoplasms of the brain

Abstract: The histopathology of two patients with radiation-induced neoplasms of the brain following therapeutic irradiation for intracranial malignancies is described. The second neoplasms were an atypical meningioma and a polymorphous cell sarcoma, respectively. They occurred 12 and 23 years after irradiation (4000 rad), within the original field of irradiation. In both cases, the radiation-induced tumors were histologically distinct from the initial medulloblastomas. Both patients were retreated with local irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(16 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Case reports present successful treatments of an example of bilateral blindness secondary to a recurrent, preirradiated hemangiopericytoma of the pituitary fossa [172], or of radiation-induced neoplasms [173]. Even a clival chordoma [174] and other skull base tumours [175,176] have been treated with an implantation of seeds, as well as locations that are a challenge for high-precision percutaneous radiotherapy [177,178].…”
Section: Reviewmentioning
confidence: 99%
“…Case reports present successful treatments of an example of bilateral blindness secondary to a recurrent, preirradiated hemangiopericytoma of the pituitary fossa [172], or of radiation-induced neoplasms [173]. Even a clival chordoma [174] and other skull base tumours [175,176] have been treated with an implantation of seeds, as well as locations that are a challenge for high-precision percutaneous radiotherapy [177,178].…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, due to base pair disruption and deoxyribonucleic acid (DNA) strand alteration, irradiation can produce neoplastic transformation 12 . Tumour development within the irradiated field constitutes a known consequence with very detrimental outcome 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Large series have shown that skull low dose irradiation (350-425cGy) for pediatric treatment of Tinea capitis increases the relative risk for developing a brain tumour by 2.6 times 18 . Likewise, malignant CNS tumours have been witnessed to evolve in animal models submitted to brain irradiation with proton or x-ray in a much higher frequency than in non-irradiated animals 13,[23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reports of an excess of brain tumours following radiation exposure involving the head (Modan et al 1974, Shore et al 1976, Colman et al 1978, Waxweiler et al 1983, Schoenberg 1991, Dierssen et al 1988, Kumar et al 1987, including groups exposed to a-irradiation from thorium dioxide (Van Kaick et al 1986, Kyle et al 1963, radium (Stebbings and Semkiw 1989), nuclear fuel material (Hadjimichael et al 1983) and plutonium (Wilkinson et al 1987) . Excesses of brain tumours in these studies were often only marginally significant .…”
Section: Discussionmentioning
confidence: 99%